Transformation of Islamic Boarding School Education to Address Moral Challenges in the Digital Era - Paramansyah, Arman; Judijanto, Loso; Trinova, Zulvia; Rahmah, St.; Zulihi, Zulihi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research aims to explore how pesantren education can be adapted to answer the moral challenges faced by the younger generation in the digital era. Using the library research method, this study analyzes literature from various sources to understand the contribution of pesantren in facing contemporary moral issues. This study integrates the findings into a theoretical framework to highlight the relevance of pesantren education in the context of digital moral challenges. The results of the study show that various moral challenges, such as cyberbullying, social media addiction, and exposure to negative content, have a significant impact on children and adolescents. This phenomenon results in a decrease in empathy, the quality of social interaction, and an increase in negative behavior in cyberspace. Through strengthening religious values, character building, discipline, and examples from the kyai, Islamic boarding school education has proven effective in forming moral, responsible, and resilient students who can face the dynamics of the times. With this holistic approach, pesantren can become a relevant and adaptive educational model to answer moral challenges in the digital era.